Interaction Pattern of Teacher Online Learning for Tenth Grade Islamic Cultural History at MAN 1 Jombang - Hidayatur Rohmah; Risa Lailatul Mufidah (SCHOOLAR: Social and Literature Study in Education, 2021)
Writing this article aims to identify the pattern of teacher-student interaction in online learning for Islamic Cultural History subjects, as well as supporting and inhibiting factors during online learning. This study uses a qualitative method with a case study approach. Data collection techniques used are interviews, observations with one key informant, namely the Islamic Cultural History teacher at MAN 1 Jombang. The results of the research conducted indicate that the interaction pattern of online learning is one-way, two-way, and all-way interaction. Even though there are interactions, there are also some obstacles, namely sometimes lack of access and also lack of good responses from students, but learning continues and develops student potential.